Testicular Abscess an Unusual Cause for Febrile Neutropenia - Tal Grenader (The Scientific World Journal)
Patients with good-risk disseminated testicular cancer are effectively managed with platinum-based chemotherapy. Febrile neutropenia is a dose-limiting event for many chemotherapy regimens. The risk of developing febrile neutropenia is related both to the chemotherapy dose and schedule, and to patient-related factors. Among patients who require ongoing chemotherapy for metastatic disease, it is very unusual for surgical complications to delay the initiation of chemotherapy. We describe a patient who developed febrile neutropenia with testicular abscess when treated with BEP 2 weeks following inguinal orchiectomy.